1995
DOI: 10.1128/jb.177.12.3504-3511.1995
|View full text |Cite
|
Sign up to set email alerts
|

A second branched-chain alpha-keto acid dehydrogenase gene cluster (bkdFGH) from Streptomyces avermitilis: its relationship to avermectin biosynthesis and the construction of a bkdF mutant suitable for the production of novel antiparasitic avermectins

Abstract: A second cluster of genes encoding the E1␣, E1␤, and E2 subunits of branched-chain ␣-keto acid dehydrogenase (BCDH), bkdFGH, has been cloned and characterized from Streptomyces avermitilis, the soil microorganism which produces anthelmintic avermectins. Open reading frame 1 (ORF1) (bkdF, encoding E1␣), would encode a polypeptide of 44,394 Da (406 amino acids). The putative start codon of the incompletely sequenced ORF2 (bkdG, encoding E1␤) is located 83 bp downstream from the end of ORF1. The deduced amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 49 publications
2
65
0
Order By: Relevance
“…In particular, engineering biosynthetic pathways of polyketide antibiotics to incorporate novel primer units is an effective way to generate analogs of existing natural products. 15,39,24 In recent reports, we and others have shown that bacterial aromatic PKSs can be engineered to synthesize rationally modified polycyclic aromatic polyketides. 24,40,41,42 Specifically, we have harnessed bimodular PKSs to produce engineered hexaketides and octaketides.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, engineering biosynthetic pathways of polyketide antibiotics to incorporate novel primer units is an effective way to generate analogs of existing natural products. 15,39,24 In recent reports, we and others have shown that bacterial aromatic PKSs can be engineered to synthesize rationally modified polycyclic aromatic polyketides. 24,40,41,42 Specifically, we have harnessed bimodular PKSs to produce engineered hexaketides and octaketides.…”
Section: Discussionmentioning
confidence: 99%
“…The gene cluster Pfl01_3463-3466 may encode for components of the branched-chain a-keto acid dehydrogenase complex. In Streptomyces avermitilis, a branched-chain a-keto acid dehydrogenase gene cluster is essential for polyketide backbone synthesis (Denoya, 1995;Yoon et al, 2004). Moreover, it was demonstrated that branched-chain amino acids can serve as precursors for Type II polyketide synthesis through pathways that are nutrient dependent (Stirrett et al, 2009).…”
Section: Differential Expression Of Ribosomal Proteins and Phage-relamentioning
confidence: 99%
“…Valine catabolism has been investigated in microbes and higher animals (4,6,13,17,19,20,22,25). There is general agreement on the initial catabolic events, which include oxidative deamination and decarboxylation to yield isobutyryl coenzyme A (isobutyryl-CoA).…”
mentioning
confidence: 99%
“…However, comparatively little attention has been devoted to the mechanisms that operate in the transition from primary to secondary metabolism and control the carbon flow for the required building blocks. Several studies have shown that valine catabolism can play an important role in supplying fatty acid precursors for macrolide and polyether antibiotic formation (4,12,14,15,17,18,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation